Question

Solve and check x-4(x-3)+7=6-(x-4)

270

likes1350 views

Dexter

4.7

98 Answers

Solution:

1. Expand the equation:

- Left side:x - 4(x - 3) + 7 = x - 4x + 12 + 7

- Right side:6 - (x - 4) = 6 - x + 4

2. Simplify both sides:

- Left side:x - 4x + 12 + 7 = -3x + 19

- Right side:6 + 4 - x = 10 - x

3. Set the simplified equations equal:

-3x + 19 = 10 - x

4. Rearrange the equation to isolate terms involvingx :

-3x + x = 10 - 19

5. Simplify:

-2x = -9

6. Solve forx :

x = \frac{-9}{-2} = \frac{9}{2}

7. Therefore, the solution forx is:

x = \frac{9}{2}

1. Expand the equation:

- Left side:

- Right side:

2. Simplify both sides:

- Left side:

- Right side:

3. Set the simplified equations equal:

4. Rearrange the equation to isolate terms involving

5. Simplify:

6. Solve for

7. Therefore, the solution for

Frequently asked questions (FAQs)

What is the variance of the data set 2, 5, 7, 9, 12?

+

What is the value of sin(pi/4) + cos(pi/3)?

+

What is the median of a set of numbers: 3, 6, 12, 15, 18?

+

New questions in Mathematics